Perencanaan Strategi Bersaing Kafe W.E.K.O.F - Gadis Mulia Reski (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In Indonesia, the café business continues to thrive because it is considered a profitable In Indonesia, the cafe business continues to thrive because it is considered profitable and worth considering. The large number of business people trying to enter the culinary business has caused competition among culinary business people to be relatively high. W.E.K.O.F Cafe must have the right business strategy to compete with competitors. This research is descriptive qualitative research with the aim of explanatory research through case studies. Data collection using a semi-structured interview method. This study uses primary and secondary data sources. Analysis of the internal and external environment is used to determine what strategy W.E.K.O.F Cafe needs now. This study uses the Value Chain to analyze the company's internal as well as using PESTEL and Porter's Five Forces to analyze the influence of the micro and macro environment on the company. SWOT analysis is used to produce strategic designs suitable for companies to implement. Then, the IFE, EFE, IE, CPM, GS, and Quantitative Strategic Planning Matrix (QSPM) matrices are used for data processing. Based on the research results, it can be concluded that the W.E.K.O.F Cafe has not been optimal in designing strategies. The owner still takes decision-making as a whole. Alternative strategy suggestions that can be done is market development.